Analytical and experimental analysis of the shear strength of bolted saw-tooth joints. Issue 5 (31st March 2022) - Lin, Hang; Sun, Penghui; Chen, Yifan; Zhu, Youyan; Fan, Xiang; Zhao, Yanlin
Abstract: For bolted joints, the influencing area of the bolt is usually considered to be the entire joint plane. Relevant studies have reported that the influencing area of the bolt ultimately becomes nearly circular, instead of extending to the entire joint plane, during shearing. To obtain the exact shear strength of the bolted joint, the equivalent shear area of the bolt (i.e. the influencing area of the bolt) was considered. Moreover, the influence coefficient m of the bolt, defined as the diameter ratio of the equivalent shear area to the bolt, was proposed to establish a modified model of the bolted joint shear strength. Via a comparison of the experimental and calculated results of the modified model, the value of m for saw-tooth joints with a single bolt was determined, and the modified model was verified.